2001
DOI: 10.1002/aoc.260
|View full text |Cite
|
Sign up to set email alerts
|

Identification of [(GS)2AsSe] in rabbit bile by size‐exclusion chromatography and simultaneous multielement‐specific detection by inductively coupled plasma atomic emission spectroscopy

Abstract: An arsenic±selenium metabolite that exhibited the same arsenic and selenium X-ray absorption nearedge spectra as the synthetic seleno-bis(S-glutathionyl) arsinium ion [(GS) 2 AsSe]À was recently detected in rabbit bile within 25 min after intravenous injection of rabbits with sodium selenite and sodium arsenite. X-ray absorption spectroscopy did not (and cannot) conclusively identify the sulfurdonor in the in vivo sample. After similar treatment of rabbits, we analyzed the collected bile samples by size-exclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 21 publications
(20 reference statements)
0
30
0
Order By: Relevance
“…Rat Mrp2 transports As(GS) 3 and MMA(GS) 2 into bile, and this is potentially important for preventing hepatotoxicty; however, these GSH conjugates are not stable at the alkaline pH of bile (Kala et al, 2000;Gailer et al, 2002;Raab et al, 2004;Yehiayan et al, 2009). This leads to their rapid dissociation, reabsorption across the intestine, and cycling back to the liver through the portal circulation (Dietrich et al, 2001;Suzuki et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Rat Mrp2 transports As(GS) 3 and MMA(GS) 2 into bile, and this is potentially important for preventing hepatotoxicty; however, these GSH conjugates are not stable at the alkaline pH of bile (Kala et al, 2000;Gailer et al, 2002;Raab et al, 2004;Yehiayan et al, 2009). This leads to their rapid dissociation, reabsorption across the intestine, and cycling back to the liver through the portal circulation (Dietrich et al, 2001;Suzuki et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The mutual detoxification between arsenite and selenite can be rationalized in terms of the in vivo formation and subsequent biliary excretion of the seleno-bis (S-glutathionyl) arsinium ion, [(GS) 2 AsSe] À (Scheme 1). 14,16,17 In vitro studies revealed that this species is rapidly formed in blood 73 and most likely assembled inside erythrocytes 74 after individual import of arsenite and selenite into these cells. 75 Intracellular metabolism of arsenite and selenite in erythrocytes to (GS) 2 As±OH/ (GS) 3 As 76 and selenide 59,70,77,78 would then allow nucleophilic attack of the latter on the arsenic atom of (GS) 2 As±OH or (GS) 3 As to give [(GS) 2 AsSe] À .…”
Section: Effect Of Toxic Metals and Metalloids On The Metabolism Of Smentioning
confidence: 99%
“…With respect to the interaction between Se(IV) and As(III), a metabolite containing both elements, the seleno-bis(S-glutathionyl) arsinium ion [(GS) 2 AsSe] − was identified in the bile of rabbits that had been injected with selenite and arsenite (Gailer et al 2000a(Gailer et al , 2002b. Further investigations have shown that [(GS) 2 AsSe] − is formed in rabbit blood and that erythrocytes mediate its assembly (Manley et al 2006).…”
mentioning
confidence: 99%